Mathematical Process Skills by Gender in Junior High Schools - Kamid; Rohati; Ramalisa, Yelli; Putri, Fhadira Insani (LPPM Undiksha, 2024)
Understanding differences in mathematical processing skills between male and female students in junior high school is very important because it can help in designing more effective teaching strategies. Therefore, this research aims to look at students' mathematical process skills based on gender in the collection material. The type of research used is quantitative research with a comparative type. The research instrument used was a questionnaire on students' mathematical processing skills. The population in this study was all junior high school students. The sample used in this research was 60 class VII A students consisting of 30 male students and 30 female students. The sampling technique in this research used simple random sampling. The data analysis techniques used in this research are descriptive analysis and inferential analysis. Descriptive data analysis is presented in a frequency distribution in the form of numbers such as mean, median, minimum value and maximum value, while inferential statistical techniques are carried out in the form of normality, homogeneity and hypothesis testing in the form of the t test. The research results showed that male students who had superior mathematical processing skills were students at SMP 21 Batanghari. Meanwhile, female students who have superior mathematical processing skills are students at Al-Arif Islamic Middle School. It was found that there were significant differences in the mathematical processing skills of male and female students at SMP 21 Batanghari and SMP Islam Al-Arif.